Monitoring and Evaluation Processes Critical to Service Provision in South Africa's Rural-Based Municipalities - Mubangizi, Betty C. (Journal of Reviews on Global Economics, 2019)
South African municipalities are at the coalface of service provision, with communities relying on municipal performance for life-impacting services. The impact of effective service delivery or the lack thereof is particularly significant for the poor who generally lack safety nets to cushion themselves against the inadequacies of poorly resourced, mainly rural, municipalities. Although municipalities are distinct entities, they rely on other levels of government for important resources. Further, municipalities draw on the support of other non-government actors to provide public services. In such a scenario, where variously positioned actors contribute to the attainment of the public good, the role of monitoring and evaluation (M & E) is critical as it ensures compliance by each of the role-players in the effective delivery of basic services to communities. What are the complexities of service delivery and the processes through which M & E takes place in rural municipalities? How are the beneficiaries of municipal services included in M & E, and what might be the critical contributors to a functional and all-inclusive M & E process in rural-based municipalities? This conceptual paper, posited in complex systems theory, draws on relevant literature to answer these questions. The conclusion drawn is that while current M & E process are, mainly, monitored through statutory structures; non-statutory structures formed out of ad hoc self-organising models can provide useful forums for monitoring municipal service provision for sustainable livelihoods.